Self-Presentation Berperan terhadap Psychological Well-Being: Survey pada Emerging Adulthood Pengguna Instagram - Nadia Vika Ferryanti; Setiasih Setiasih; Ni Putu Adelia Kesumaningsari (Jurnal Ilmiah Psikologi MIND SET, 2021)
Social media is one of the media that is often used as a medium of interaction and self-presenting. The use of social networking sites helps individuals form relationships with others online so that individuals have good psychological well-being. Uploading videos, photos or statuses is part of an online self-presentation so that what is presented can shape identity. The purpose of the study was to find out the relationship of self-presentation with psychological well-being. The method used is quantitative correlational. The number of participants in the study was 282 active students used instagram. Instruments used in this study is Ryff’s Psychological well-being Scale and Self-Presentation on Facebook Questionnaire from Michikyan et al. The results showed that is significant positive correlation of self-presentation with psychological well-being of emerging adulthood which used instagram. The more often individuals do self-presentation on instagram in the form of real self, the higher the psychological well-being condition of the individual, while the individual who conducts self-presentation ideally self or false self then the psychological well-being level is likely to be low.